The Effect of Motivation to Employee Performance: Case Study ABX EKSPRESS SDN BHD - Nur Izzati Husna Abd Rahman (2016)
The purpose of the study is to identify the problems having by the ABX Ekspress Sdn Bhd, and to prepare the collected information to choose and implement possible solution for recognized issues. This study focus on the effect motivation to employee performance. Therefore, the study collects the data from industry by analysing of interview transcripts. A special emphasis is given to analysing the problems of the company in their human resources. This study will then identify the related issues based on employee performance and motivation in their workers in the company. The study identified a number of issues related to the lack of motivation in each employee has been obtained by the three main issues of remuneration, recruitment, Job performance and job satisfaction. The study also concluded that the employer must give more reward, the management and co-workers need to cooperate in work and always support each other. The human resources necessary to employ more closely and according to the characteristics of the set, but also provide a reasonable job with the salary offered.